Some Unified Integrals for Generalized Mittag-Leffler Functions - Prakash Singh; Shilpi Jain; Carlo Cattani (Axioms, 2021)
Here, we ascertain generalized integral formulas concerning the product of the generalized Mittag-Leffler function. These integral formulas are described in the form of the generalized Lauricella series. Some special cases are also presented in terms of the Wright hypergeometric function.